Speech Style Analysis: Sociolinguistic Perspective - Taufiq Kurniawan; Lala Nining Indrawa; Siti Danti (Departement of Mathematics Education, 2023)
The prompt development of English has formed a new perception that English should be the language of daily life. Diverse studies have been carried out to extend knowledge about the language itself with the various methods used. The researcher, in this context, aims to examine the speech style used by the main actor and the racial conflict that happened in the movie of “Freedom Writer”. The researcher uses a socio-linguistic approach to get a better understanding of the context of the speech and the speech style that is used according to the context. The film was based on a real story that happened in the united stated. The film was released in 2007. The researcher found a variety of speech style that was used by the main actor in the movie. The most dominant speech style used in the film is “Formal Style”. The formal style is used in an important and serious situation such as lectures, sermons, television newscasts, and some other occasions. The language style that is rarely used in this film is the “Frozen” style because the style is used in certain literature. More complexed discussion in this movie regarding racial issues were also further discussed.